Burnup Performance of a PBR with an Accumulative Fuel Loading Scheme Utilizing Burnable Poison Particles in UO2 and ROX Fuels. (December 2017) - Simanullang, Irwan Liapto; Obara, Toru
Abstract: The accumulative fuel loading scheme is a promising design for pebble bed reactors (PBRs). In a previous study, burnup analysis for such a reactor was performed using UO2 fuel and the results showed that the maximum burnup and operation period were 223 GWD/t and 10.2 years, respectively. In this study, rock-like oxide (ROX) fuel was analyzed in PBR with an accumulative fuel loading scheme. The results showed that a maximum burnup and operation period of 218 GWd/t and 8.4 years, respectively. However, high excess reactivity occurred in the initial condition for both UO2 and ROX fuels. In this study, burnable poison (BP) particles were used to suppress the initial excess reactivity. Several BP materials such as B4 C, Gd2 O3, Er2 O3 and CdO were investigated. In case of UO2 fuel, the combination of B4 C and Gd2 O3 was found to be optimal for flattening the reactivity swing in the initial condition. However, due to the fissile density of ROX fuel being about five times lower than that of UO2 fuel, single-material BP particles (B4 C) seemed to be optimal for flattening the reactivity swing. By utilizing the BP particles at the initial condition, the results of UO2 and ROX fuels showed that maximum keff was decreased from 1.423 to 1.068 and from 1.357 to 1.033, respectively. On the other hand, the maximum discharge burnup value and core lifetime were quite similar to the results for the reactor that did not use BP particles at the initial condition.